GEOCHEMISTRY OF TITANIUM AND ITS MODES OF OCCURRENCE IN METASOMATICALLY ALTERED ROCKS AT SKARN DEPOSITS - Aleksandrov S.M.; Troneva M.A. (My University, 2003)
In this paper, we discuss the sequential variation in the modes of occurrence of titanium in the process of magnesian skarn and calc-skarn formation as a manifestation of prograde metasomatism of carbonate rocks at contacts with intrusions of various compositions. We considered the incorporation of Ti as an amphoteric element into simple and composite oxides from titanates to borates and its isomorphism in rock-forming silicates. It was shown that titanates and titanoborates with a variable magnesium content and the Mg/Ti ratio varying from 0 to 5 largely occur in magnesian skarn, whereas perovskite and Ti-bearing silicates are typical of calc-skarn. Magmatic fluids are considered to be a major Ti source, and authigenic Ti derived from altered carbonate rocks is of subordinate importance. In the minerals under consideration, Ti is isomorphically replaced by Sn, V, Fe, and Al. The chemical compositions of titanates, borates, and silicates from skarn deposits are reported; titanates from magnesian calciphyres are compared by composition with the respective minerals from carbonatites of similar major-element chemistry.